2019
DOI: 10.1088/1361-665x/ab3d18
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fused deposition modeling process parameters on the transformation of 4D printed morphing structures

Abstract: 4D printing combines additive layer manufacturing processes with smart materials to create structures that are able to change shape or properties over time under the influence of environmental stimuli. The article presents 3D printed multi-material shape-variable structures imitating a hinge. Fused deposition modelling was used because it provides the ability to pre-program structures during the printing process by varying printing parameters. The structures are printed with PLA and TPU and remain flat after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The printing speed influences the shape transformation. Higher printing speed produces higher residual stress and as a result, higher shrinkage ratio [ 9 , 15 , 28 , 29 , 30 ]. Higher printing speed also leads to a less accurate extrusion process and lower print quality [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The printing speed influences the shape transformation. Higher printing speed produces higher residual stress and as a result, higher shrinkage ratio [ 9 , 15 , 28 , 29 , 30 ]. Higher printing speed also leads to a less accurate extrusion process and lower print quality [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the second case, it is controlled by the multi-material structure, consisting of active and passive segments. For the active segment, a combination of polymers that differ in thermal transition temperatures and have different physical and mechanical properties is used [ 9 , 15 ]. One of the polymers, the active one, shrinks when heated above its Tg, and the second polymer, called the passive material, remains unchanged and serves only as a support for the active material to twist in a certain direction and plane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kačergis et al [ 72 ] studied 3D-printed multi-material shape-variable structures imitating a hinge. Using the FFF process, different printing parameters were analysed.…”
Section: Shape Memory Effect In Polymeric Compositesmentioning
confidence: 99%
“…The possibility of Thermoform opens a few future avenues for the SMPC world, such as remote activation of the 3 D printed shape. Following this work, Kacergis et al investigated the printing parameters for 4 D printing based on bilayer PLA/TPU composites but suggested that surrounding heat activation might not be the best choice to achieve field applications of 4 D printing (Kačergis et al, 2019). Garces and Ayranci (2018), Garces and Ayranci (2020) proposed the 3 D printing of SMPU with a Graphene oxide/PLA bilayer composite.…”
Section: Multi-materials Shape Memory Polymer Compositesmentioning
confidence: 99%